Rancang Bangun Content Management System Wedding Invitation Berbasis Web Multimedia Menggunakan Metode Object Oriented Hypermedia Design - Detila Rostilawati; Dede Kurniadi; Ridwan Setiawan (Jurnal Algoritma, 2022)
Digital invitations are a trend that is in demand, one of which is a wedding invitation. Digital invitations are in great demand because of the ease with which they can be distributed using social media without the need to deliver them to the homes of those invited. Content management wedding invitations aim to be able to assist users in managing wedding invitations so that it becomes easier with invitation customization and invitation distribution that can quickly reduce paper usage and assist in admin financial management. This study uses the Object-Oriented Hypermedia Design Method (OOHDM) using the stages used in building a multimedia web-based wedding invitation content management system, namely the stages of domain analysis, navigational design, abstract interface design, and implementation. The results obtained are in the form of a content management system that can assist users in creating and managing and designing wedding invitations according to their wishes, can assist admins in managing finances, print financial reports automatically and also helps users to create or manage invitations. By using the wedding invitation content management system, technological results are obtained that can contribute to helping information provision activities within the scope of wedding invitations to become more modular and reusable, assisting users in the process of managing wedding invitations, customizing the appearance as desired, assisting admins or web managers in managing financial reports by saving time in searching financial data by date.